2008
DOI: 10.1530/rep-08-0099
|View full text |Cite
|
Sign up to set email alerts
|

Ovary and uterus transplantation

Abstract: Ovarian and uterine transplantation are procedures gaining more attention again because of potential applications in respectively fertility preservation for cancer and other patients and, more tentatively, women with uterine agenesis or hysterectomy. Cryopreservation of tissue slices, and possibly whole organs, is providing opportunities for banking ovaries for indefinite periods before transplanting them back to restore fertility. The natural plasticity of this organ facilitates grafting to different sites wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 80 publications
0
20
0
Order By: Relevance
“…If the donor and host were genetically unrelated and the host's immune system was competent, there was a heavy infiltration of leucocytes within a week that quickly rejected the grafts. Immunotolerance was also not induced between mouse strains (Gosden 2007(Gosden , 2008. So far, in order to facilitate these experiments, most studies have used immunodeficient or inbred mice as recipients to reduce/eliminate rejection after ovarian transplantation (Candy et al 2000, Hosoe et al 2008, Schubert et al 2008, Soleimani et al 2008, Abir et al 2009, Motohashi et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…If the donor and host were genetically unrelated and the host's immune system was competent, there was a heavy infiltration of leucocytes within a week that quickly rejected the grafts. Immunotolerance was also not induced between mouse strains (Gosden 2007(Gosden , 2008. So far, in order to facilitate these experiments, most studies have used immunodeficient or inbred mice as recipients to reduce/eliminate rejection after ovarian transplantation (Candy et al 2000, Hosoe et al 2008, Schubert et al 2008, Soleimani et al 2008, Abir et al 2009, Motohashi et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, genes involved in inflammatory and immune response were upregulated. However, it is intriguing to observe the experimental studies which demonstrated that the XT ovarian tissues collected from a wide array of mammalian species are capable of producing steroid hormones that maintain estrous cycles, form antral follicles (Gosden 2008), and in some cases develop into cleavage stage embryos after IVF (Senbon et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although he sometimes used model species, as a clinical investigator he was far more constrained than animal physiologists who could incorporate controls into their experiments. Nevertheless, he was able to conclude from his case series that the ovary is an organ of ''internal secretion,'' and he became a zealot for the emerging science of endocrinology, a founder member of During the past 2 decades the annual number of original articles reporting ovarian transplantation has risen steeply from close to zero (12). Gosden the Endocrine Society, and an early proponent of endocrine therapy, which his work had anticipated.…”
Section: Appreciation Overduementioning
confidence: 99%